1971
DOI: 10.1128/aem.21.4.639-642.1971
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline Inhibition of a Lipase from Corynebacterium acnes

Abstract: A lipase which hydrolyzes triglycerides (tricaprylin and trilaurin) and naphthyl laurate was obtained from the broth of Corynebacterium acnes cultures by ammonium sulfate fractionation. Ca2+ and sodium taurocholate stimulated activity of the enzyme. Ethylenediaminetetraacetic acid (EDTA) did not inhibit activity of the Ca2+-activated enzyme, but lipolytic activity was inhibited by EDTA in the absence of Ca2+. Tetracycline (10-4M) produced a slight inhibition of the lipase activity with 5 X 10-5 M or less showi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Freinkel et al (1965) assumed tetracycline to be bacteriostatic and mediate its effect by reducing numbers of P. acnes. Shalita & Wheatley (1970) postulated that tetracycline directly inhibited the lipases on the skin surface and Hassing (1971 a) and Weaber et al (1971) demonstrated the inhibition of P. acnes lipase in uitro. Cunliffe et al (1973) showed a decrease in free fatty acid levels in skin surface lipids of patients on long-term tetracycline therapy, which was associated with a clinical improvement in their acne with no change in the numbers of P. acnes.…”
Section: The Microbial Lipase Theorymentioning
confidence: 99%
“…Freinkel et al (1965) assumed tetracycline to be bacteriostatic and mediate its effect by reducing numbers of P. acnes. Shalita & Wheatley (1970) postulated that tetracycline directly inhibited the lipases on the skin surface and Hassing (1971 a) and Weaber et al (1971) demonstrated the inhibition of P. acnes lipase in uitro. Cunliffe et al (1973) showed a decrease in free fatty acid levels in skin surface lipids of patients on long-term tetracycline therapy, which was associated with a clinical improvement in their acne with no change in the numbers of P. acnes.…”
Section: The Microbial Lipase Theorymentioning
confidence: 99%
“…A corollary of this thesis was the belief that the major mode of action in successful antibiotic therapy was the indirect eflTect of reducing free fatty acids by lowering P. acnes populations. Several workers also showed that P. acnes lipase is inhibited in vitro by tetracyclincs, suggesting that the drop in skin surface fatty acids might be due to a direct inhibition of lipase by tetracyclines (Hassing 1971;Puhvel & Rcisner, 1972;Weaber, Freedman & Eudy, 1971). The relevance of this flnding was diminished, however, by the realization that the amount of tetracyclines required to inhibit lipase activity was far above therapeutically attainable doses (Puhvel & Reisner, 1972).…”
mentioning
confidence: 99%
“…THE ORGANISM Propionibacterium acnes has been implicated in the disease acne vulgaris (Voss 1976) and has been shown to produce a lipase (Kellum et a/. 1970;Puhvel & Reisner 1970;Hassing 1971;Weaber et al 1971) a hyaluronidase and a protease (Marples & McGinley 1974). These substances, and other biologically active compounds (enzymic, antigenic or chemoattractant) could be involved in the pathogenesis of acne vulgaris (Holland et al 1978).…”
mentioning
confidence: 99%